On Musical Topics and Tropes. Definitions, History, Theoretical Amplifications, Pedagogical Applications, and Extensions - Hatten, Robert S. (Res Facta Nova, 2025)
This overview of the current state of musical topic theory is organized in six parts: definitions and scope of the theory, origins and development of the theory since 1980, reflections on reconstructing a tacit competency for interpreting topics and tropes, a pedagogical approach to categorizing topics and tropes based on markedness theory, analysis and interpretation of topical troping in three brief Classical examples, and contributions to theorizing topics and tropes both before and after the Classical era.